Design of Micro-Bluetooth Motion Acquisition System - Benkun Bao; Senhao Zhang; Mostafa Orban; Donghai Qiu; Hongbo Yang; Xiankai Cheng (Shock and Vibration)
To realize the digitization of infant motion information and explore more abundant human health information with motion information to facilitate early treatment, a micro-Bluetooth motion acquisition system is designed. The low-power design of the micro-Bluetooth motion capture sensor in the system and intelligent algorithm for optimizing the precision of the infant movement measured angles can realize the system’s sustainable use and data reliability. With the help of collecting and analyzing human arm, leg, and head movement information, we can recognize that the system can carry out more research and experiments on natural infant movements.